Deteksi Dini Penyakit Arteri Perifer pada Pasien Diabetes Melitus di Kota Mataram - Yanna Indrayana; Herpan Syafii Harahap; Ilsa Hunaifi (Jurnal Gema Ngabdi, 2020)
Diabetes mellitus is currently becoming a major public health problem in the world. The prevalence of diabetes mellitus globally in 2019 is estimated at 9.3% and will increase to 10.9% in 2040. Peripheral artery disease is one of the important complications of diabetes mellitus. Patients with diabetes mellitus accompanied by peripheral artery disease have high morbidity and. Therefore, early detection of peripheral artery disease in diabetic patients is important. This event is carried out with the aim of early detection of peripheral artery disease in diabetes mellitus sufferers in Mataram. A total of 183 diabetes mellitus patients at the Siti Hajar Hospital, Mataram, were participated in this event, with an average age of 57 years and 67.8% of them were women. Most of the patients (75.4%) had poor blood glucose control. Of these, 26.8% of patients had peripheral artery disease. Patients and/or caregivers showed high enthusiasm during the education regarding the detection results of the peripheral artery disease. This event was very useful in increasing the knowledge of diabetic patients, especially in terms of blood sugar control, prevention, and management of peripheral artery disease.